Women who have undergone female genital mutilation/cutting's perceptions and experiences with healthcare providers in Paris. Issue 4 (6th April 2022) - Azadi, Bahar; Tantet, Claire; Sylla, Fatoumata; Andro, Armelle
Abstract: Female genital mutilation/cutting (FGM/C) is a health and human rights issue and a dangerous form of gender-based violence. Given migratory flows from the countries in which it is practised, FGM/C concerns a substantial number of women living in Western countries. In this study, we looked at women who had undergone FGM/C experiences with French medical practitioners. We also discussed with them the desirability of screening for, and prevention of, FGM/C in international travel medicine centres. A qualitative approach was used to collect and analyse the data. Focus groups and semi-structured interviews were held with 26 women (24 participants in focus groups and 2 individual interviews). Transcriptions were coded and analysed thematically. All the participants came from sub-Saharan Africa. Their median age was 32.9 years. Persistent silence about FGM/C in the host society following immigration resulted in dissatisfaction with healthcare providers. Participants expected professionals to address the subject of FGM/C, feeling professionals should bring up the subject first so as to put women at ease. International travel medicine centres were discussed by some as a possible means of prevention.